2001
DOI: 10.4050/jahs.46.210
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Rotor Airfoil Testing in the UK

Abstract: c f k M P Pm R RAE v 1Y ama 1 Q' nnll P w Peter G. Wilhy Corrrrrltr~,,r Westlarid Helicoprer,~ Lir~riled, Yeo~,il, Sos~ersel, Et~glnnd, UKThe current capability for evaluating airfoil characteristics has developed over a period of some 25 years, during which time some twentv airfoils have heen tested in the Aircraft Research Association's transonic wind-tunnel dvnamic facilitv. The availability of this test facility has been a key element in the development of a rotor design philosophy, which is to avoid exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Obviously, this may not necessarily be the case for other aerofoils or higher Mach numbers. Wilby (2) compared three stall-onset criteria, namely C N maximum, C m break and trailing-edge pressure diverging/leading-edge suction collapsing, for the RAE-series aerofoils and concluded that these three criteria cannot be used to identify stall onset with any precision. Wilby chose the leading-edge suction peak/collapse, which rises with angle-of-attack in attached flow, but collapses when the flow separates (dynamic vortex detaches from the leading-edge region), as the indicator of dynamic stall onset.…”
Section: P Deviationmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, this may not necessarily be the case for other aerofoils or higher Mach numbers. Wilby (2) compared three stall-onset criteria, namely C N maximum, C m break and trailing-edge pressure diverging/leading-edge suction collapsing, for the RAE-series aerofoils and concluded that these three criteria cannot be used to identify stall onset with any precision. Wilby chose the leading-edge suction peak/collapse, which rises with angle-of-attack in attached flow, but collapses when the flow separates (dynamic vortex detaches from the leading-edge region), as the indicator of dynamic stall onset.…”
Section: P Deviationmentioning
confidence: 99%
“…The pitching moment hysteresis can cause a negative damping when the aerofoil oscillates about the stalling angle causing the rotor blades to experience stall flutter. Stall flutter ultimately defines the flight envelope of the rotor and serious effort has been expended in developing aerofoil sections that can delay the stalling point as in the case of the RAE 9000-series aerofoils developed by Wilby (1,2) under the British Experimental Rotor Programme (BERP).…”
Section: Introductionmentioning
confidence: 99%
“…The universality of dynamic stall and the stall delay effect as well as the special flow characteristics makes this topic attractive. Researchers have long been investigating the phenomenon via both experimentation [2][3][6][7][8][9][10][11][12] and numerical simulations [1,[13][14][15]. Some researchers also developed semi-empirical relations of oscillating thin airfoil theory to predict the forces and moment [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…In the relevant research, the initial focus was placed on the airfoil, the overall design and tip configuration of the blades. Wilby (2001), Leishman (2006), Dadone (1978) and Yamauchi and Johnson (1983) present new, multi-section airfoils capable of elevating the lift-to-drag ratio and reducing the impact of stalling and shock [1][2][3][4]. Leishman (2006) shows that a reasonable nonlinear twist distribution design will result in the blade span-wise aerodynamic distribution is more uniform [2], and thus enhances aerodynamic efficiency.…”
Section: Introductionmentioning
confidence: 99%